Potential of Metarhizium from soils and rhizosphere of diversified coffee systems in insect suppression and its indirect effect on a coffee pest through endophytic association - Franzin, Mayara Loss (2021)
Diversified crop systems enhance ecosystem services, such as pest biological control, via attraction and maintenance of entomophagous, and improve soil chemical and biological characteristics. Soil entomopathogenic fungi, such as Metarhizium spp., are also benefit in diversified systems, because these systems reduce direct soil irradiation and increase soil humid. The fungi of this genera are important microbial control agents of insect pests, which made them an important tool to pest management. Besides, this genus is also considered as endophytic, colonizing roots of plants, increasing plant growth and promoting protection against pests. Here, we designed a strategic diversified coffee system in the Cerrado of Minas Gerais, by the associating coffee with plants that attract natural enemies, and investigated the effects of such diversification in the Metarhizium conservation in soil. Coffee was associated with trees of Inga edulis (Fabaceae) and Senna macranthera (Fabaceae) and perennial bushes of Varronia curassavica (Cordiaceae). Non-crop plants were maintained between coffee rows, except before the coffee harvesting, as they can provide food resources for predators and parasitoids. As control, we designed plots with conventional coffee monoculture, with the standard conventional use of pesticides. In Chapter 1, we evaluated Metarhizium activity and density, soil chemical characteristics and enzymatic activity from diversified and conventional soil of coffee systems over time. We estimated the coffee yield in both coffee systems by measuring the volume of coffee fruits per plant and the weight of 100 fruits. The activity and density of Metarhizium spp. was assessed using the bait survival technique with Tenebrio molitor (Coleoptera: Tenebrionidae) larvae as bait, and plating soil suspensions on to solid selective media for counts of colony-forming units (CFU), respectively. Twelve months after experiment starts, bait insects died two times faster due to Metarhizium spp. in the diversified than in the conventional coffee systems, while the density of Metarhizium spp. was also higher in the diversified. Beta-glycosidase activity was greater in the diversified coffee system, indicating more organic matter decomposition and carbon cycle in this coffee system. Furthermore, there was no difference of volume of fruit between coffee systems, however, the weight of 100 fruits was higher in diversified system in 2021. In Chapter 2, we investigatedMetarhizium spp. rhizosphere association with plant roots from diversified and conventional coffee system. We used the same protocols of Chapter 1 to evaluated Metarhizium activity and density. Both were higher in soil and roots samples from diversified than conventional system. We isolated Metarhizium spp. from I. edulis, V. Curassavica, S. macranthera, Gnaphalium spicatum, Conyza bonariensis, Solanum Americanum, Ageratum conyzoides, Bidens pilosa, Sida cordifolia and coffee plants of diversified coffee system. In Chapter 3, we investigate whether Metarhizium robertsii and Metarhizium brunneum, isolated from coffee roots from diversified coffee system in Cerrado, improve coffee seedlings growth and indirectly protect them against the coffee leaf miner (CLM) Leucoptera coffeella (Lepidoptera: Lyonetiidae). We recovered Metarhizium spp. from most of coffee seedling roots, indicating that these fungi can colonize coffee roots by soil drench. We found that M. robertsii increased the leaf area of coffee seedlings. Besides, the plants inoculated with Metarhizium isolates had lower percentage of mined leaf area and the development time of CLM was higher in these plants. Therefore, in this thesis we showed that strategic plant diversification in coffee crops increases density and activity of Metarhizium, soil enzymatic activity and coffee yield over time. Besides, M. brunneum and M. robertsii have potential to use as inoculates of coffee seedlings, because the plants inoculated with them isolates showed lower CLM damage. Therefore, strategic plant diversification in coffee systems can be an alternative to monocultures, improving soil quality and coffee yield. Keywords: Diversified crop. Arabica coffee. Entomopathogenic fungal. Endophytic fungal. Supressive soil